IMPLEMENTATION OF INTEGRATED AUTHENTIC THEMATIC ASSESSMENT IN THE 2013 CURRICULUM AT MIN SIDOARJO PACITAN 2016/2017 - Imam Machali; efi tri Astuti (Sunan Kalijaga International Journal on Islamic Educational Research, 2017)
Assessment is a key component for knowing the effectiveness ofthe learning process. The assessment method should have relevance withthe curriculum that applied in the educational institution. In the 2013curriculum, the relevant assessment method is an authentic assessment.This authentic assessment method measures the competence of attitudes,skills and knowledge of the students based on their processes and outcomes.This method is different with the previous curriculum assessment methodsthat always emphasize cognitive competence (knowledge) and tend to beoriented to exam results, in authentic assessment teachers always payattention to the balance competency between attitude competencyassessment, knowledge and skills that agree with the development ofcharacteristics according of student's steps. Based on the research,implementation of the authentic assessment at MIN Sidoarjo Pacitan didn’toptimally. Caused, the teacher’s ability of technical authentic assessment arenot capable.